2021
DOI: 10.1002/cac2.12158
|View full text |Cite
|
Sign up to set email alerts
|

The role of the HIF‐1α/ALYREF/PKM2 axis in glycolysis and tumorigenesis of bladder cancer

Abstract: Background: As a rate-limiting enzyme of glycolysis, pyruvate kinase muscle isozyme M2 (PKM2) participates in tumor metabolism and growth. The regulatory network of PKM2 in cancer is complex and has not been fully studied in bladder cancer. The 5-methylcytidine (m5C) modification in PKM2 mRNA might participate in the pathogenesis of bladder cancer and need to be further clarified. This study aimed to investigate the biological function and regulatory mechanism of PKM2 in bladder cancer. Methods:The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 58 publications
1
88
0
Order By: Relevance
“…And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ). In previous study, researcher identified hypoxia can induced the sumolytion of m 6 A enzyme( Hou et al, 2021 ), hypoxia-inducible factor-1 alpha (HIF-1α) can drive m 5 C modification to promote tumorigenesis( Wang J. Z. et al, 2021 ), m 1 A and m 6 A modification can significantly affect the infiltration of immune cells( Cai et al, 2021 ; Gao et al, 2021 ), m 7 G modification can drives immune evasion ( Devarkar et al, 2016 ), and m 6 A, m 7 G modification can induce EMT in cancer development ( Yu X. et al, 2020 ; Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…And RNA methylation highly interconnected with hypoxia, immune response and EMT( Lin et al, 2019 ; Chao et al, 2020 ; Wang E. et al, 2021 ). In previous study, researcher identified hypoxia can induced the sumolytion of m 6 A enzyme( Hou et al, 2021 ), hypoxia-inducible factor-1 alpha (HIF-1α) can drive m 5 C modification to promote tumorigenesis( Wang J. Z. et al, 2021 ), m 1 A and m 6 A modification can significantly affect the infiltration of immune cells( Cai et al, 2021 ; Gao et al, 2021 ), m 7 G modification can drives immune evasion ( Devarkar et al, 2016 ), and m 6 A, m 7 G modification can induce EMT in cancer development ( Yu X. et al, 2020 ; Xia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…m5C methylation is regulated by “writer, reader, and eraser” regulators that affect tumor progression under abnormal conditions ( 51 , 52 ). A comprehensive analysis of m5C regulators and their associated lncRNAs can help clarify the role of m5C modification patterns on LGG tumor cells and guide more effective individualized therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…According to the staining intensity, they were divided into three categories: 1 (mild), 2 (moderate), and 3 (severe), respectively. The two scores are multiplied to get the final score: low expression group [1] , [2] , [3] , [4] and high expression group [6] , [7] , [8] , [9] , [10] , [11] , [12] . The objects are classified by pathologists who had no access to clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…ALYREF has been found to be upregulated in a number of malignancies and is connected with poor prognosis, including bladder cancer, glioblastoma, and head and neck squamous cell carcinoma. [8] , [9] , [10] , [11] , [12] . Xue et al [13] have pointed out that ALYREF might be a prognostic factor for HCC.…”
Section: Introductionmentioning
confidence: 99%